2003
DOI: 10.1021/ol035649y
|View full text |Cite
|
Sign up to set email alerts
|

Switchable Catalysis:  Modular Synthesis of Functionalized Pyrimidinones via Selective Sulfide and Halide Cross-Coupling Chemistry

Abstract: [reaction: see text] A general demonstration of orthogonal selectivity of the Liebeskind-Srogl cross-coupling protocol compared to the Suzuki-Miyaura and Stille variants is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
46
0
4

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(50 citation statements)
references
References 9 publications
(11 reference statements)
0
46
0
4
Order By: Relevance
“…It has been reported that methylation of 2-thiouracil gives a 2-methylthio derivative. 19,20) This tendency was also verified in the case of 3-substituted 2,4-dithiouracil 4b. The preference of substitution on the sulphur atom could be explained by strong nucleophilicity of the 2-sulfide anion formed by treatment of 4b with a strong base.…”
mentioning
confidence: 54%
“…It has been reported that methylation of 2-thiouracil gives a 2-methylthio derivative. 19,20) This tendency was also verified in the case of 3-substituted 2,4-dithiouracil 4b. The preference of substitution on the sulphur atom could be explained by strong nucleophilicity of the 2-sulfide anion formed by treatment of 4b with a strong base.…”
mentioning
confidence: 54%
“…Again, this reaction proceeded equally well with arylamines bearing electron-withdrawing and electron-donating substituents. [40,42,43] Although not optimized, it is reported therein for the first time with a 6-phenylthiopurine heterocycle, expanding the scope of this useful reaction. All these reactions were performed under the conditions of Table 1, Entry 6 with the exception of sulfonamides 7a and 7b, for which the reaction was carried out at 100°C overnight.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, 5-halouracilas can be used as synthetic intermediates in coupling reactions. 5 In this work we present the synthesis of 5-bromo uracils (14-17), the Bromacil analogous, through a methodology quickly and efficiently.…”
Section: Introductionmentioning
confidence: 99%